Étienne Pasquier, un avocat à l’éloquence herculéenne dans la République des Lettres - Baptiste Robaglia (Clio@Themis)
This article deals with the identification of Étienne Pasquier with the civilizing eloquence of the Gallic Hercules. In the troubled context of the 16th century, the jurist-humanist identified himself with this eloquence that he implemented with the aim of participating in the civilization undertaken by the Republic of Letters. Pasquier thus took care to disseminate his knowledge, but also to civilize royal acts by confronting them with an ideal of justice. Behind this double meaning of eloquence then emerges the features of the Gallic hero described by Lucien de Samosate.